Forensic examinations in the investigations of crimes involving animals: a review - Cristiano Mougenot Mores; Márcio Botelho de Castro; Cristiano Barros de Melo (Ciência Rural)
ABSTRACT: In the investigation of crimes involving animals and animal-origin products or by-products, forensic veterinary medicine plays a crucial role through examinations and analyses of evidence related to the cases. In addition to veterinary forensics, other forensic sciences frequently contribute to solving these types of crimes. Drawing on the extensive experience of the Federal Police’s criminal investigations in Brazil and the specialized forensic veterinary and scientific expertise developed at the stricto sensu Graduate level at the University of Brasília, this review provides an updated and comprehensive analysis of the most relevant expert examinations supporting investigations into animal-related crimes, with a focus on the Brazilian context. The review covers key aspects of forensic examinations conducted by criminal experts, including forensic entomology, forensic toxicology, imaging techniques, taxonomic identifications, bird rings, investigations of mistreatment, forensic veterinary pathology, forensic genetics, and isotope ratio analysis. The field of veterinary forensics, with its diverse resources, established techniques, highly trained and continually updated experts, and the latest advancements in criminalistics, is essential for properly addressing judicial demands.